Place as a Metaphysical Problem in Albert the Great and Thomas Aquinas - Kamel, Onsi A. ca. 20./21. Jh. (2025)
Thomas Aquinas’ particular synthesis of Aristotelianism and Neoplatonism, and the intellectual tradition it inaugurated, has at least twice faced critical challenges from developments in physics. Besieged by the sixteenth and seventeenth century novatores and more or less ignored by the nineteenth- and twentieth-century practitioners of mathematical physics, Thomism was nevertheless forced, in both cases, to reckon with the relationship of metaphysics to physics and the related question of the nature of scientific theories. This essay begins with two opposed twentieth-century Thomist responses to these challenges, that of Pierre Duhem and that of the River Forest Thomist school. Then, after carefully examining the concept of place in Albertus Magnus’ untranslated De Natura Loci and commentary on the Liber de Causis, putting this element of Albert's natural philosophy into conversation with Thomas Aquinas’, and investigating Thomas’ account of the ordering of the sciences, I argue that both approaches, opposites though they are, fail. Neither adequately accounts for a crucial and much-neglected feature of Albert's and Thomas’ conception of the relationship between the sciences: the dependence of metaphysics upon various deliverances of natural philosophy.